Biochar from Biomass Slow Pyrolysis. Issue 1 (October 2020) - Cai, Nan; Zhang, Huili; Nie, Jiapei; Deng, Yimin; Baeyens, Jan
Abstract: Pyrolysis is widely used in the chemical industry to produce e.g. carbon black from heavy fuel oil (HFO) and coke from coal, to convert post-consumer plastic waste into chemicals, to transform heavier hydrocarbons into lighter ones, and to thermo-chemically treat biomass. Whereas a lot of work has been presented on the fast pyrolytic production of bio-oil from biomass, the objectives of biochar and added-value chemicals are now a major focus when using biomass in a slow pyrolysis reactor. Fast pyrolysis targets mostly bio-oil (up to 60 or 70 wt%). Slow pyrolysis targets mostly biochar (up to ∼60 wt%), together with 25-30 wt% of bio-oil and the balance as gas. The paper presents results from biomass pyrolysis in the slow operating mode and assesses the products formed and their application perspectives.